Seed treatment methods and duration effects on germination of wild sunflower - Akinola, J.O.; Larbi, Asamoah; Farinu, G.O.; Odunsi, A.A. (2000)
The effects were evaluated of six methods and six durations of seed treatment on the germination of wild sunflower (Tithonia diversifolia) seeds. The treatments were as follows: (1) hot water at 80 °C, (2) hot water at 100 °C, (3) oven-drying at 80 °C, (4) oven-drying at 100 °C, (5) immersion in concentrated sulphuric acid and (6) immersion in 10% hydrogen peroxide. The durations were 0, 2.5, 5, 10, 15 and 20 min. Treatment with hot water at 80 or 100 °C for 11–14 min, and oven-drying at 100 °C for 20 min all resulted in more than 65% germination 10 d after treatment. Oven-drying at 80 °C, immersion in concentrated sulphuric acid and in 10% hydrogen peroxide resulted in less than 50% germination. Based on the higher cumulative germination, lower cost, and environmental concerns, hot water treatment at 80 or 100 °C for 11–15 min is recommended.